Charge carrier dynamics of 2-dimensional photoelectrodes probed via ultrafast spectroelectrochemistry - Austin, Rachelle, author; Sambur, Justin, advisor; Krummel, Amber, advisor; Rappe, Anthony, committee member; Prieto, Amy, committee member; McNally, Andrew, committee member; Brewer, Samuel, committee member (Colorado State University. Libraries, 2024)
The integration of hot charge carrier-based energy conversion systems with two-dimensional (2D) semiconductors holds immense promise for enhancing the efficiency of solar energy technologies and enabling novel photochemical reactions. Current approaches, however, often rely on costly multijunction architectures. In this dissertation, I present research that combines spectroelectrochemical and in-operando transient absorption spectroscopy measurements to unveil ultrafast (<50 fs) hot exciton and free charge carrier extraction in a proof-of-concept photoelectrochemical solar cell constructed from earth-abundant monolayer (ML) MoS2. Theoretical analyses of exciton states reveal enhanced electronic coupling between hot exciton states and neighboring contacts, facilitating rapid charge transfer. Additionally, I discuss insights into the physical interpretation of transient absorption (TA) spectroscopy data in 2D semiconductors, comparing historical perspectives from physical chemistry and solid-state physics literature. My perspective encompasses various physical explanations for spectral features and experimental trends, particularly focusing on the contribution of trions to TA spectra. Furthermore, I examine how different physical interpretations and data analysis procedures can yield distinct timescales and mechanisms from the same experimental results, providing a comprehensive framework for understanding charge carrier dynamics in 2D semiconductor-based optoelectronic devices.
Keywords: electrochemistry; spectroelectrochemistry; ultrafast spectroscopy; solar; 2-dimensional materials; spectroscopy